Subjective and objective nutritional assessment: nurses' role and the effect of cultural differences - M. Gbareen; S. Barnoy; M. Theilla (BMC, 2021)
Abstract Background Even though the nutritional assessment of chronically ill patients has a significant effect on outcomes, nurses' time constraints in clinical encounters may make the process impractical. Also, cultural background has an effect on nutritional assessment. Patient nutritional self-assessment can ease some of the nurses' workload. Objectives: To compare tools for subjective and objective nutritional assessment and to examine cultural differences in nutritional assessment between Jews and Arabs living in Israel. Methods The research design was cross-sectional; data were collected from Jews and Arabs with chronic illnesses living in the community during their visit to a public health clinic. The admitting nurse performed an objective nutritional assessment (Mini Nutritional Assessment (MNA)) after the patients completed the Subjective Nutritional Assessment (SANS). The data were analyzed using descriptive statistics, Pearson's correlation coefficients were calculated to test the relationships between the variables, and independent student t-tests were used to compare the means and differences between groups. The diagnostic accuracy of the MNA and of the SANS was determined using the area under the curve (AUC) analysis of receiver operating characteristic (ROC) curves. The agreement between the MNA and SANS measurements was estimated by a Bland Altman plot. The level of significance employed throughout the analysis was 0.05. Results The sample was a convenience sample of 228 chronically ill patients, consisting of 121 Arabs and 107 Jews. A significant correlation was found between the subjective and objective nutritional assessments. The Bland-Altman plot demonstrated that the SANS and the MNA have a high level of agreement. Using the area under the curve (AUC) analysis of receiver operating characteristic (ROC) curves, showed an moderate diagnostic accuracy (73 % sensitivity and 30 % specificity). Conclusions Since the patient-completed nutritional assessment requires minimal time investment by nurses and we found a significant correlation and evidence for the accuracy and agreement of the objective and subjective assessments, further studies should assess and validate the possibility of replacing the objective nutritional assessment by the subjective assessment. Cultural background has a significant effect on patients' nutritional self-assessment; hence, culture should be considered as part of the nutritional assessment.